The Linguistics of Slang: Understanding Gen Z’s Digital Language on TikTok - Lutfi Kurnia; Sigit Haryanto (JELITA, 2026)
This study investigates the use of slang by Generation Z on the social media platform TikTok, focusing on the Indonesian context. As digital communication becomes increasingly integrated into daily life, slang emerges as a linguistic tool for identity expression, creativity, and group affiliation. The research employs a qualitative-descriptive approach supported by observation, document analysis, and interviews with Gen Z TikTok users. A total of 32 slang terms were identified and analyzed based on their forms, functions, and sociocultural implications. The findings reveal that TikTok slang is not only influenced by global digital trends but also localized through code-mixing with Bahasa Indonesia. Slang functions as a medium for humor, critique, solidarity, and participation in viral content, reflecting the dynamic linguistic practices of digital youth. This study contributes to digital sociolinguistics by highlighting how audiovisual platforms like TikTok shape the evolution of language in informal online spaces.